Qur'anic Character Formation Through the Living Qur'an Approach - Nurul Aisyah; Syamsu Nahar (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Character formation is a fundamental mission of Islamic education, as morality is the foundation for sustaining a nation’s dignity. Specific Background: In the context of Islamic boarding schools (pesantren), the Living Qur’an approach integrates Qur’anic values into daily routines, fostering spiritual, moral, and social excellence. Knowledge Gap: While previous studies affirm the benefits of the Living Qur’an, few deeply examine its implementation process, supporting and inhibiting factors, and its holistic impact on students’ character. Aims: This study explores the process, supporting elements, and challenges in forming Qur’anic character through the Living Qur’an at Ikhwanul Hasanah Civil Boarding School. Results: Using a qualitative case study method with observation, interviews, and documentation, findings show that Qur’anic character—faith, piety, discipline, responsibility, and love for the Qur’an—is cultivated through classroom learning, extracurricular activities, pesantren culture, and community engagement. Novelty: This research provides an in-depth, process-oriented analysis that links daily habituation, role models, and institutional culture with comprehensive character formation. Implications: The Living Qur’an proves to be an effective pedagogical model for producing religious, morally grounded individuals prepared to become Rabbani leaders, despite challenges of diverse student backgrounds and limited teaching staff. Highlights: Integrates Qur'anic values into daily routines. Shapes faith, piety, and discipline holistically. Effective despite challenges in resources and backgrounds. Keywords: Qur'anic Character, Living Qur'an, Islamic Boarding School, Character Education, Faith Formation